New Approach of Dipterocarpus alatus Oil as a Permeation Enhancer in Ibuprofen Gel - Daodee, Supawadee; Monthakantirat, Orawan; Chulikhit, Yaowared (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Yang-na tree has a scientific name as Dipterocapus alatus Roxb. Ex G.Don in family Dipterocarpaceae. Many parts of this tree can be used especially for D. alatus oil. Objectives: To develop basic formula of ibuprofen gel composed of D. alatus oil as a permeation enhancement agent from natural source. Materials and Methods: This study composed of formulation development, physico-chemical property testing, permeation study and stability study. Results: The suitable ibuprofen gel formulation consisted of 0.5 percent D. alatus oil for carbopol and 1 percent D. alatus oil for carboxymethylcellulose as gelling agent when evaluated by side-by-side diffusion cell and physico-chemical properties. Conclusion: This study could get the basic ibuprofen gel formula containing D. alatus oil as the permeation enhancer which gave the value added of this oil to apply and use in pharmaceutical.
Keywords: Dipterocapus alatus; Ibuprofen; Permeation enhancer; Carbopol; Carboxymethylcellulose; Gel